A 10-bp deletion in the apolipoprotein epsilon gene causing apolipoprotein E deficiency and severe type III hyperlipoproteinemia - Feussner, Giso; Dobmeyer, Jürgen; Gröne, Hermann-Josef; Lohmer, Stefan; Wohlfeil, Stefan (The American journal of human genetics, 1996)
Type III hyperlipoproteinemia (HLP) is usually associated with homozygosity for apolipoprotein (apo) E2. We identified a 30-year-old male German of Hungarian ancestry with severe type III HLP and apo E deficiency. The disease was expressed in an extreme phenotype with multiple cutaneous xanthomas. Apo E was detectable only in trace amounts in plasma but not in the different lipoprotein fractions. Direct sequencing of PCR-amplified segments of the apo epsilon gene identified a 10-bp deletion in exon 4 (bp 4037-4046 coding for amino acids 209-212 of the mature protein). The mutation is predictive for a reading frameshift introducing a premature stop codon (TGA) at amino acid 229. By western blot analysis, we found small amounts of a truncated apo E in the patient's plasma. Family analysis revealed that the proband was homozygous--and 10 of 24 relatives were heterozygous--for the mutation. Heterozygotes had, as compared to unaffected family members, significantly higher triglycerides (TG), very low-density lipoprotein (VLDL) cholesterol and a significantly higher VLDL cholesterol-to-serum TG ratio, which is indicative of a delayed remnant catabolism. We propose that the absence of a functionally active apo E is the cause of the severe type III HLP in the patient and that the mutation, even in a single dose in heterozygotes, predisposes in variable severity to the phenotypic expression of the disease.
Gesehen am 27.01.2025